Global and China burden of hormone-related cancers and risk factors, 1990–2021: results from the Global Burden of Disease Study 2021 - Xiaoyu Hu; Jingjing Lv; Chang Qin; Xiaoxuan Liu; Jianbiao Zhu; Yongchun Cui (BMC Public Health)
Abstract Background Updated data on hormone-related cancers (HRCs) are crucial for their prevention, management, and treatment, aligning with the UN's Sustainable Development Goals. This study focuses on HRCs: breast, thyroid, uterine, ovarian, prostate, and testicular cancers. Despite their significance, comparative studies on these cancers are limited. Methods Data for incidence, prevalence, mortality, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs) related to HRCs were obtained from the Global Burden of Disease Study 2021. Statistical analyses were performed using R and Joinpoint Software. Age-standardized rates (ASR), percentage changes (1990–2021), annual percent change (APC) and average annual percent change (AAPC) are used to examine trends and risk factors associated with HRCs across various years, genders, and age groups, both in China and globally. Findings In 2021, China reported 659450 incidence cases of six HRCs, including 527009 cases (95% UI: 398030, 684814) in females and 132442 cases (89701, 181113) in males, reflecting a 29.97% increase since 1990. Deaths attributed to HRCs totaled 176526, with 130281 cases (99207, 166654) among females and 46245 cases (33049, 62510) among males, marking an 11.07% increase during the same period. The age-standardized incidence rates (ASIR) for HRCs in China were 10.70 (38.19, 65.86) per 100,000 for females and 13.87(9.50, 18.71) for males, in contrast to global rates of 17.07(62.11, 72.57) for females and 39.21(35.75, 41.69) for males. Age-standardized death rates (ASDR) were 3.54(9.22, 15.50) for females and 5.86(4.16, 7.83) for males, compared to higher global ASDRs of 6.17(19.49, 22.98) and 13.73(12.06, 14.78),respectively. From 1990 to 2021, China and the global population saw significant increases in ASIR for most cancers, except global ovarian cancer (AAPC = -0.229). Female HRCs mortality, YLLs, and DALYs declined significantly, particularly for uterine cancer. Conversely, Chinese males experienced increased mortality, YLLs, and DALYs for breast and thyroid cancers. Testicular cancer prevalence increased among Chinese males (AAPC = 7.329). Specifically, female breast cancer mortality in China decreased from 2011 to 2014 (APC = -2.82). Uterine cancer mortality dropped sharply from 2011 to 2015 (APC = -7.91). Thyroid cancer mortality declined from 2000 to 2007 (APC = -3.54), while ovarian cancer mortality decreased from 2000 to 2004 (APC = -3.33). Male breast cancer incidence peaked around 2010, and testicular cancer incidence rose significantly from 2011 to 2015 (APC = 7.77). All above changes were statistically significant (P < 0.05). Regarding age distribution characteristics, female HRCs consistently peak in the 60–74 age group globally and in China, whereas male HRCs show greater variability. In this age bracket, female breast cancer incidence reaches 348.90 (270.60, 440.16) in China versus 483.55 (449.97, 516.08) globally, while uterine cancer rates are 71.74 (52.18, 99.03) in China compared to 151.71 (138.55, 163.03) worldwide. Similarly, ovarian cancer peaks at 39.29 (28.29, 51.02) in China and 69.95 (63.59, 75.55) globally. Prostate cancer incidence also peaks in this group, with rates of 121.87 (84.48, 168.23) in China contrasting sharply with 534.72 (491.27, 568.09) globally. Conversely, testicular cancer shows a distinct pattern, peaking in the younger age group of 25–44 years, with incidences of 5.95 (4.44, 7.85) in China and 19.21 (18.04, 20.56) globally. The 25–44 age group also remains significant for thyroid cancer, with incidences of 23.31 (17.01, 32.52) in China and 31.57 (27.61, 36.30) globally. In terms of risk factors, smoking contributed to an ASR of 0.22 (0.16, 0.27) deaths globally, while alcohol accounted for 0.39 (0.27, 0.54) deaths. In China, low physical activity resulted in an ASR of 0.18 (0.03, 0.33) deaths, where high BMI notably increased risks for female HRCs. Environmental factors significantly impacted global ovarian cancer, contributing 0.12 (0.06, 0.19) deaths, while smoking influenced prostate cancer mortality, with an ASR of 0.36 (0.16, 0.60) deaths. Interpretation Our study reveals that rising incidence rates and age-specific patterns of female HRCs in China and globally are largely associated with shifts in lifestyle and dietary habits. To address this issue, it is essential to implement tailored prevention strategies for different cancer types and age groups and enhance management of risk factors, especially considering the growing burden of diseases affecting the elderly due to population aging.